2020
DOI: 10.3390/jcm9082552
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Carcinomas with Intestinal-Type Metaplasia/Differentiation: Does Mismatch Repair System Defects Matter? Case Report and Systematic Review of the Literature

Abstract: Background: Intestinal metaplasia/differentiation in primary endometrial carcinomas is an uncommon phenomenon, with only few cases described. Material and Methods: We performed a systematic review of endometrial carcinomas with intestinal metaplasia/differentiation interrogating the electronic databases Pubmed, Web of Science, and Scopus, and we reported an additional case arising in a 49-year-old woman. Results: We identified only eight patients diagnosed with endometrial carcinomas exhibiting intestinal meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Therefore, it appears appropriate to consider GTEC together with non-endometrioid carcinomas in terms of patient management. Regarding the cases of EEC with gastrointestinal differentiation, a recent review suggested that they might be more aggressive than pure EC and associated with a MMRd signature [ 78 ]. Further studies are warranted in this regard.…”
Section: Gastric-type Carcinoma (Gtec)mentioning
confidence: 99%
“…Therefore, it appears appropriate to consider GTEC together with non-endometrioid carcinomas in terms of patient management. Regarding the cases of EEC with gastrointestinal differentiation, a recent review suggested that they might be more aggressive than pure EC and associated with a MMRd signature [ 78 ]. Further studies are warranted in this regard.…”
Section: Gastric-type Carcinoma (Gtec)mentioning
confidence: 99%
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review was performed according to the PRISMA guidelines [ 64 ], searching in multiple databases as previously described [ 61 , 62 , 65 ]. The study aimed to answer the following PICOS (Population, Intervention, Comparison, Outcomes) questions…”
Section: Methodsmentioning
confidence: 99%